Molecular genetic analysis of the F11 gene in 14 Turkish patients with factor XI deficiency: identification of novel and recurrent mutations and their inheritance within families - (:unkn) unknown (SIMTI SERVIZI SRL, 2018)
Background. Factor XI (FXI) deficiency is an autosomal bleeding disease associated with genetic defects in the F11 gene which cause decreased FXI levels or impaired FXI function. An increasing number of mutations has been reported in the FXI mutation database, most of which affect the serine protease domain of the protein. FXI is a heterogeneous disorder associated with a variable bleeding tendency and a variety of causative F11 gene mutations. The molecular basis of FXI deficiency in 14 patients from ten unrelated families in Turkey was analysed to establish genotype-phenotype correlations and inheritance of the mutations in the patients' families. Material and methods. Fourteen index cases with a diagnosis of FXI deficiency and family members of these patients were enrolled into the study. The patients' F11 genes were amplified by polymerase chain reaction and subjected to direct DNA sequencing analysis. The findings were analysed statistically using bivariate correlations, Pearson's correlation coefficient and the non-parametric Mann-Whitney test. Results. Direct DNA sequencing analysis of the F11 genes revealed that all of the 14 patients had a F11 gene mutation. Eight different mutations were identified in the apple 1, apple 2 or serine protease domains, except one which was a splice site mutation. Six of the mutations were recurrent. Two of the mutations were novel missense mutations, p.Val522Gly and p.Cys581Arg, within the catalytic domain. The p.Trp519Stop mutation was observed in two families whereas all the other mutations were specific to a single family. Discussion. Identification of mutations confirmed the genetic heterogeneity of FXI deficiency. Most of the patients with mutations did not have any bleeding complications, whereas some had severe bleeding symptoms. Genetic screening for F11 gene mutations is important to decrease the mortality and morbidity rate associated with FXI deficiency, which can be life-threatening if bleeding occurs in tissues with high fibrinolytic activity.
Keywords: FXI deficiency; F11 gene; rare bleeding disorders; coagulation deficiency; RARE BLEEDING DISORDERS; COAGULATION-FACTOR-XI; FXI DEFICIENCY; THROMBIN GENERATION; BLOOD-COAGULATION; ASHKENAZI JEWS; CLASSIFICATION; QUESTIONNAIRE; ACTIVATION; PHENOTYPE